2018
DOI: 10.14445/22490183/ijbtt-v8i1p601
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micro Tuber Formation in Potato (Solanum tuberosum L.): is there any Relation between Methyl Jasmonate, Sugars, and Explants?

Abstract: Studies on potato (Solanum tuberosum L.) plants have been carried out to plant tissue culture laboratories because of the disease and virulent free seed tubers in field conditions. Since generative production in commercial potato production is not economically massive, production is made more economically with tubers. Jasmonic acid (JA) and its related compounds are newly recognized plant growth regulators and they are known to have effects on many physiological processes. In this study, it was aimed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Wang and Hu (1982) and Badoni and Chauan (2010) also reported that the optimum condition for in vitro tuberization of virusfree potatoes were in a medium containing BAP at 10 mg.l 1 . Vural et al (2018) used BAP (2.5 mg.l 1 ) with NAA (0.5 mg.l 1 ) in their in vitro micro propagation of potato and found that these cytokinins had a positive effect on micro tuber forma tion and can be recommended to use them commer cially in mass production.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and Hu (1982) and Badoni and Chauan (2010) also reported that the optimum condition for in vitro tuberization of virusfree potatoes were in a medium containing BAP at 10 mg.l 1 . Vural et al (2018) used BAP (2.5 mg.l 1 ) with NAA (0.5 mg.l 1 ) in their in vitro micro propagation of potato and found that these cytokinins had a positive effect on micro tuber forma tion and can be recommended to use them commer cially in mass production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the high level of sucrose which represents the milestone in the culture medium for microtuber induction in potato, the plant growth regulator in particular the cytokinins proved to be essential for enhancing microtuberization in different potatoes genotypes. Many studies were used BAP for increasing the production of microtubers in potato (Aboshama et al 2006;Momena et al 2014;Dhaka and Nailwal, 2015;Mohapatra et al 2016;Emaraa et al 2017;Khalil et al 2017;Moreno et al 2017;Salem And Hassanein, 2017;Ali et al 2018;Vural et al 2018;Borna et al 2019;Hossain et al 2019;Naqvi et al 2019;Khorsandi et al 2020;Refaie et al 2020;Sembiring et al 2020;Sota et al 2020;Andriani et al 2021).…”
Section: The Effect Of Bap and Tdz On Microtuberization In Potato CV ...mentioning
confidence: 99%
“…Propagation of potato plants can be achieved in several ways, including tuber sprouts, tuber cuttings, and true seeds. It has also been reported that in vitro systems based on a single-nodal stem explant result in the differentiation of stolon into a tuber instead of a leafy shoot when placed on a tuber-inducing medium, which is characterized by a high sucrose content and by supplementation with tuber-inducing plant growth substances, and incubated in the dark (Xu et al, 1998;Fernie and Willmitzer, 2001;Vural et al, 2018). Here, we report the effects of hypergravity in a centrifuge on potato tuber formation using single-nodal stem segments from the aspects of soluble sugar and starch content, as well as the effect of hypergravity on stem growth.…”
Section: Introductionmentioning
confidence: 99%